Effect of Lidocaine 2% Versus Bupivacaine 0.5% and 1 Versus 2 Dual Separate Injections on Onset and Duration of Ultrasound-Guided Wrist Blocks: A Blinded 2 × 2 Factorial Randomized Clinical Trial. (7th February 2022) - Van Boxstael, Sam; Lopez, Ana M.; Balocco, Angela Lucia; Vandepitte, Catherine; Meex, Ingrid; Duerinckx, Joris; Kuroda, Maxine M.; Mesotten, Dieter; Van Herreweghe, Imre; Hadzic, Admir
Abstract : BACKGROUND: Local anesthetics are often selected or mixed to accomplish faster onset of anesthesia. However, with ultrasound guidance, local anesthetics are delivered with greater precision, which may shorten the onset time with all classes of local anesthetics. In this study, we compared onset time and duration of ultrasound-guided wrist blocks with a fast onset versus a longer lasting local anesthetic administered via single or dual (spatially separate) injections at the level of the midforearm. METHODS: In this randomized clinical trial, 36 subjects scheduled for carpal tunnel release were randomly assigned to receive ultrasound-guided median and ulnar nerve blocks with lidocaine 2% or bupivacaine 0.5% via single or dual injections ( n = 9 in each group). Subjects fulfilled the study requirements. The main outcome variables were onset and duration of sensory blockade, which were tested separately in 2 (drug) × 2 (injection) analysis of variances (ANOVAs) with interaction terms. RESULTS: Sensory block onset time did not differ significantly between subjects given lidocaine 2% (9.2 ± 3.4 minutes) or bupivacaine 0.5% (9.5 ± 3.1 minutes) ( P = .76; mean difference, −0.3 ± 1.1 minutes [95% confidence interval CI, −2.5 to 1.9]) or between the single- (9.6 ± 2.8 minutes) and dual- (9.1 ± 3.6 minutes) injection groups ( P = .69; mean difference, −0.4 ± 1.1 minutes [95% CI, −1.8 to 2.6]). Sensory duration was longer for subjects in the bupivacaine 0.5% group (27.3 ± 11.6 hours) than for subjects in the lidocaine 2% group (8.4 ± 4.1 hours) ( P < .001; 95% CI, 12.7–25.1). However, sensory duration in the single- (15.7 ± 12.5 hours) and dual- (19.4 ± 13.1 hours) injection groups did not differ significantly ( P = .28; mean difference, −3.7 ± 4.3 hours [95% CI, −12.6 to 5.1]). CONCLUSIONS: No significant effect was found for onset time between lidocaine 2% and bupivacaine 0.5% used in ultrasound-guided wrist blocks. Dual injections did not shorten onset time. Since mean nerve block duration was longer with bupivacaine 0.5%, our results suggest that the selection of local anesthetic for the median and ulnar nerves at the level of the midforearm should be based on the desired duration of the block and not on its speed of onset.